2000
DOI: 10.1002/(sici)1097-0169(200004)45:4<279::aid-cm4>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between elongation factor-1? and microtubules in vivo is domain dependent and conditional

Abstract: Although the precise definition for a microtubule‐associated protein (MAP) has been the subject of debate, elongation factor‐1α (EF‐1α) fits the most basic criteria for a MAP [Durso and Cyr, 1994a]. It binds, bundles, stabilizes, and promotes the assembly of microtubules in vitro, and localizes to plant microtubule arrays in situ. In this study, the in vitro and in vivo association of EF‐1α with microtubules was further investigated. Analysis of the in vitro binding data for EF‐1α and microtubules indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 66 publications
(69 reference statements)
1
15
0
Order By: Relevance
“…In general, protein synthesis can be enhanced by a close spatial association of the ribosome and other factors involved in translation with the cytoskeleton (2,31,57). eEF1A interacts with actin filaments, tubulin, and the ER and apparently mediates the general attachment of cellular mRNA to the cytoskeleton (2,3,13,31,45). TMV genomic RNA is associated with the plant cytoskeleton and ER throughout the infection cycle (42).…”
Section: Discussionmentioning
confidence: 99%
“…In general, protein synthesis can be enhanced by a close spatial association of the ribosome and other factors involved in translation with the cytoskeleton (2,31,57). eEF1A interacts with actin filaments, tubulin, and the ER and apparently mediates the general attachment of cellular mRNA to the cytoskeleton (2,3,13,31,45). TMV genomic RNA is associated with the plant cytoskeleton and ER throughout the infection cycle (42).…”
Section: Discussionmentioning
confidence: 99%
“…eEF1A can undergo posttranslational modifications, such as methylation and phosphorylation, and can interact with various proteins, including tubulin, calmodulin and actin. It has been suggested that eEF1A may regulate the cytoskeleton by promoting and stabilizing microtubule assembly in plants potentially in response to auxin signalling or changes in intracellular calcium levels (Moore and Cyr 2000). There is evidence that specific eEF1A isoforms, with variation in actin binding motifs, may be expressed in rapidly elongating maize tissue (Carneiro et al 1999).…”
Section: Sdg20smentioning
confidence: 99%
“…Elongation factor-1␣ (EF-1␣), which is involved in protein translation (Browning, 1996), binds MTs in the presence of weak lipophilic acids (Moore and Cyr, 2000) and undergoes Ca 2ϩ -mediated proteolysis in the presence of PLD␣ Tobacco BY-2 protoplasts, prepared after preincubation with 10 M taxol, were treated with calcium and detergent and then processed for immunofluorescence microscopy using double labeling with antibodies against p90 and ␣/␤-tubulin as in Figure 7. (A) and (B) Cortical MTs were removed from the protoplast ghosts by cold treatment in the presence of 5 mM CaCl 2 for 30 min.…”
Section: Possible Role Of Plasma Membrane-pld-mt Associationmentioning
confidence: 99%
“…from castor bean (Ransom-Hodgkins et al, 2000). EF-1␣ can bind, bundle, stabilize, and promote the assembly of MTs in vitro (Moore and Cyr, 2000, and references cited therein), and it also binds and bundles actin (Liu et al, 1996). Thus, EF-1␣ has the potential to be an effector of signals to both the MT and actin cytoskeletons.…”
Section: Possible Role Of Plasma Membrane-pld-mt Associationmentioning
confidence: 99%